End to end congestion control and bandwidth measurement in high speed ATM networks - S. Mascolo; A. Grieco; E. Di Sciascio; M. Gerla (ATM 2000. Proceedings of the IEEE Conference on High Performance Switching and Routing (Cat. No.00TH8485), 2000)
We propose an end to end congestion control algorithm for ABR traffic in high-speed ATM networks. The algorithm is designed using a control theoretic approach and the Smith (1959) principle is proposed as a tool to design the feedback control law. The algorithm is executed at the entry node of ATM networks and switches do not execute either any computation or stamp any explicit feedback on RM cells. In particular, we propose that the traffic source at the entry node computes the input rate by estimating the bottleneck queue level. This estimate is done by stamping time into RM cells to measure round trip times, and by measuring available bandwidth. The available bandwidth is measured by sending probe RM cells and by measuring the rate of returning RM cells.
Keywords: Bandwidth; Communication system traffic control; Traffic control; Asynchronous transfer mode; Algorithm design and analysis; Time measurement; Feedback control; Switches; Computer networks; Probes